What are the Required Elements Needed to Create an Effective Visual Art Intervention for People Living with Dementia? A Systematic Review. Issue 2 (3rd April 2022) - Shoesmith, Emily; Charura, Divine; Surr, Claire
ABSTRACT: Although there has been growing interest in visual art interventions for people with dementia, there is a restricted evidence base regarding their theoretical basis. To address this gap, this systematic literature review explored how and why visual art interventions work in dementia care. Common features of successful visual art interventions were identified, including: intervention 'dose, ' session content, participant choice, artistic ability, the role of the facilitator/therapist, group work, and setting. Understanding the mechanisms and/or processes of visual art interventions is important for future development, evaluation, and implementation.